A divergent Pseudomonas aeruginosa palmitoyltransferase essential for cystic fibrosis‐specific lipid A. Issue 1 (27th November 2013) - Thaipisuttikul, Iyarit; Hittle, Lauren E.; Chandra, Ramesh; Zangari, Daniel; Dixon, Charneal L.; Garrett, Teresa A.; Rasko, David A.; Dasgupta, Nandini; Moskowitz, Samuel M.; Malmström, Lars; Goodlett, David R.; Miller, Samuel I.; et al.
Summary Strains of Pseudomonas aeruginosa (PA) isolated from the airways of cystic fibrosis patients constitutively add palmitate to lipid A, the membrane anchor of lipopolysaccharide. The PhoPQ regulated enzyme PagP is responsible for the transfer of palmitate from outer membrane phospholipids to lipid A. This enzyme had previously been identified in many pathogenic Gram‐negative bacteria, but in PA had remained elusive, despite abundant evidence that its lipid A contains palmitate. Using a combined genetic and biochemical approach, we identified PA1343 as the PA gene encoding PagP. Although PA1343 lacks obvious primary structural similarity with known PagP enzymes, the β‐barrel tertiary structure with an interior hydrocarbon ruler appears to be conserved. PA PagP transfers palmitate to the 3′ position of lipid A, in contrast to the 2 position seen with the enterobacterial PagP. Palmitoylated PA lipid A alters host innate immune responses, including increased resistance to some antimicrobial peptides and an elevated pro‐inflammatory response, consistent with the synthesis of a hexa‐acylated structure preferentially recognized by the TLR4/MD2 complex. Palmitoylation commonly confers resistance to cationic antimicrobial peptides, however, increased cytokine production resulting in inflammation is not seen with other palmitoylated lipid A, indicating a unique role for this modification in PA pathogenesis.